PERTANGGUNGJAWABAN PEMEGANG SAHAM ATAS PERSEROAN PAILIT YANG DINYATAKAN TERUTANG PAJAK - Gusfen Alextron Simangunsong; Budiman Ginting; Sunarmi Sunarmi; Utary Maharani Barus (Universitas Sumatera Utara, 2016)
ABSTRACT A shareholder is not always liable for the number of stocks he has remitted when the corporation sustains a loss, include are liable for the paying off all debts of a bankrupt corporation. How is the liability of legal entity of a bankrupt corporation which is in tax liability according to tax law and how is the liability of shareholders for a bankrupt corporation which is in tax payble according to tax law? The liability of legal entity of a bankrupt corporation which is stated as tax payble according to tax law becomes the liability of a curator to organize the property of the bankrupt corporation stipulated in Article 32, paragraph 1, letter b of UUKUP. A curator begins to do his job and to take liability since the verdict on bankruptcy is handed down by the Commercial Court. Majority shareholders are liable for the paying off all debts of a bankrupt corporation which is in tax payble according to Article 21 in conjunction with Article 32 of UUKUP, based on public interest in which the State acts as the preference curator. Majority shareholders have the authority to determine the policy and decision making in performing the activities of corporation. Government must be make a law or regulation to supervise curator in organizing the inventory of bankruptcy in paying off tax layble of a bankrupt corporation. Majority shareholders must be liability for the paying off the debts of a bankrupt corporation which is in tax liability, Shareholders should take individual liability when the minimum requirement of the shareholders is not fulfilled, counted if shareholders have bad faith or are illegal. Keywords: Liability, Legal Entity, Shareholder, Bankruptcy, Bankrupt Corporation, Tax Liability